Translating Fagunwa: decoding and recoding metaphor (2016)
There are existing studies on D. O Fagunwa ’s novels from different perspectives, such as tradition, religion, myth and morality. On the contrary, his translated works have not been given much attention. This study therefore content-analyses codification of metaphor in Fagunwa’s Ogbojii Ode ninu Igbo Irunmale(2005) translated into French by Olaoye Abidye as Le Preux Chasseux dans la Foret lnfestee de Demons (T989). It adopts the combination of Bassnett’s decoding and recoding in translation process and Newmark’s approach to translating metaphor. Bassnett posits that the translator operates on criteria that transcend pure mechanical re-rendering and a process of decoding and recoding is on stage. The idea of a code unit is isolated, interpreted and recoded with the TL sign unit which carries the notional image. The study examines 25 metaphoric expressions extracted from Fagunwa’s aforementioned novel from both Yoruba and French versions respectively. Metaphor is brought to the fore, beyond literal or figurative perspectives, as an indispensable element of the semiotic system with which writers generate secondary semantic extension from primary reference thereby expressing socio-cultural values, beliefs and traditions in a profound yet concise manner. The paper thus concludes that the process of decoding and recoding African metaphors exposes the translator to several hurdles most especially when it (translation) involves languages of alien cultures like French. Abioye is justified in his systemic reproduction of some metaphoric elements from the Source Text Culture to the Target Text context